(untitled) (International Journal of Food and Nutritional Sciences, 2022)
IT and ITES have become a major force to help organizations achieve their objectives. IT Industry itself has evolved over the years bringing in a lot of changes to satisfy the needs of these customers. Today we live in an ever changing world where growth is imperative. For all organizations, big or small, immediate response to new requirements by their customers has become mandatory for survival. Customer delight is the key to have repeat customers.